2015
DOI: 10.1128/aem.00959-15
|View full text |Cite
|
Sign up to set email alerts
|

AguR, a Transmembrane Transcription Activator of the Putrescine Biosynthesis Operon in Lactococcus lactis, Acts in Response to the Agmatine Concentration

Abstract: bDairy industry fermentative processes mostly use Lactococcus lactis as a starter. However, some dairy L. lactis strains produce putrescine, a biogenic amine that raises food safety and spoilage concerns, via the agmatine deiminase (AGDI) pathway. The enzymatic activities responsible for putrescine biosynthesis in this bacterium are encoded by the AGDI gene cluster. The role of the catabolic genes aguB, aguD, aguA, and aguC has been studied, but knowledge regarding the role of aguR (the first gene in the clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 59 publications
3
34
0
Order By: Relevance
“…4). The binding sites of regulators of the LuxR type, such as those of LuxR (24), PimM (a positive regulator of pimaricin biosynthesis) (25), and AguR (a transmembrane transcription activator of the putrescine biosynthesis operon in Lactococcus lactis), usually display dyad symmetry (26). Comparing these binding sites with the CerR binding box (GSAATWTTSC [S ϭ C or G; W ϭ A or T]), we found that the inverted repeated sequence of CerR shows an 8-bp match with PimM binding sites (TAGGGAATTCCCPA) but has no sequence similarity with those of the other two transcription regulators.…”
Section: Discussionmentioning
confidence: 99%
“…4). The binding sites of regulators of the LuxR type, such as those of LuxR (24), PimM (a positive regulator of pimaricin biosynthesis) (25), and AguR (a transmembrane transcription activator of the putrescine biosynthesis operon in Lactococcus lactis), usually display dyad symmetry (26). Comparing these binding sites with the CerR binding box (GSAATWTTSC [S ϭ C or G; W ϭ A or T]), we found that the inverted repeated sequence of CerR shows an 8-bp match with PimM binding sites (TAGGGAATTCCCPA) but has no sequence similarity with those of the other two transcription regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a recent in silico structure analysis predicted the AguR of a L. lactis subsp . cremoris cheese isolate to be a transmembrane protein with a typical LuxR_C‐like HTH DNA‐binding cytoplasmic C‐terminal motif (Linares and others ). This predicted AguR differs from that of Str.…”
Section: Biosynthesis Pathways Of Basmentioning
confidence: 99%
“…mutans AguR which is cytoplasmic. Further characterization of the lactococcal AgDI cluster showed that aguR gene is expressed constitutively at low levels into AguR protein which functions as a 1‐component transduction system (Linares and others ). These authors suggested that the lactococcal AguR would play a pivotal role in both sensing the presence of agmatine in the extracellular medium and interacting with the aguB promoter (P aguB ) to activate the transcription of the aguBDAC operon into polycistronic mRNA to be translated into the 4 catabolic genes of the AgDI system.…”
Section: Biosynthesis Pathways Of Basmentioning
confidence: 99%
“…The aguR gene is transcribed as a monocistronic mRNA from its own promoter P aguR , independently of the aguBDAC genes. These latter genes are co-transcribed in a single polycistronic mRNA from the promoter of the first gene of the operon (P aguB ) (Linares et al, 2015). AguR is a transmembrane protein that functions as a one-component signal transduction system: it senses the agmatine concentration of the medium and regulates the transcription of the aguBDAC operon accordingly via a C-terminal cytoplasmic DNAbinding domain (Linares et al, 2015).…”
Section: Introductionmentioning
confidence: 99%